Pengaruh literasi keuangan, motivasi investasi dan modal minimal terhadap minat investasi saham mahasiswa UNIPA Maumere - Da Silva, Dona Maria Evanca; Yuniningsih, Yuniningsih (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The interest in investing in Indonesia in recent years has tended to be dominated by young people aged 30 years and under. This can be seen from the increasing number of investment galleries located on several campuses throughout Indonesia as one of the programs from the IDX to provide education about investment to students. The purpose of this study was to determine the effect of financial literacy, investment motivation, and minimal capital on interest in stock investment in UNIPA Maumere students. This study is a quantitative study using primary data sourced from questionnaires distributed to students Faculty of Economics using a purposive sampling technique. The population in this study were students of the 2018 and 2019 Faculty of Economics. The analytical technique used in this study was PLS (Smart Partial Least Square). The results of this study indicate that financial literacy and investment motivation affect student interest in stock investment, while minimum capital does not affect student stock investment interest.